PSYCHOLOGICAL FEATURES OF RADIATION RISK PERCEPTION - Нresko, Maryna (PSYCHOLOGICAL JOURNAL, 2017)
The purpose of the study was to determine the subjective features of the perception of radiation risk and to determine its place among other hazards in the remote period after the Chernobyl disaster. Object and methods: Participated in the study: 122 liquidators (group 1); 76 liquidators, who were also evacuated from the exclusion zone (group 2); 118 people evacuated from the exclusion zone (group 3). The comparison group was 84 people (group 4). 81 participants of the ATО (5 - group) were also interviewed. Results of the study: In the comparison group, significantly less (p<0.001) fewer persons with hypertrophied perception of radiation threat compared to the main groups. The highest percentage of respondents with hypertrophied perception of radiation threat are in group II (81,54%), where respondents were exposed to the risk of exposure and evacuation as a result of the Chernobyl accident. In the group of ATO participants there are 31,34% of persons with hypertrophied perception of radiation threat. The actual “national conflicts” factor currently occupies among the groups affected by the Chernobyl accident: 22nd, 26th and 18th ranked place, 17th in the comparison group, while among the participants of the ATO - 11th place. However, the high concern of ATО participants with such a radiation factor as the diseases associated with the presence of radioactive substances in the environment (rank 7), caused by using a “dirty bomb” in the territory of the ATO, can lead to additional traumatic effects on ATО participants and will intensify the maladaptive reactions. A high assessment of the radiation hazard of the I, II and III groups interviewed, indicates the relevance for them of such a stressful event in their life as an accident at the Chernobyl nuclear power plant. The hypertrophied perception of the radiation threat in groups of liquidators and evacuees from the exclusion zone correlates with heightened concern about the nuclear industry, the presence of radioactive substances in air, soil, and products (p<0,001). Inadequate perception of radiation risk correlates with the degree of psychological stress from the Chernobyl accident (in all groups p <0.001), the degree of psychological stress from evacuation (II p<0,001, III p<0,01), concern about possible accidents and malfunctions to this time at the Chernobyl nuclear power plant (I and II p<0,001, III p<0,05) with concern about the effect of radiation on health (p<0,001), social changes (p<0,001) and negative changes in the economic situation due to the Chernobyl accident (p<0,001). Conclusions: Problems of radiation safety after the Chernobyl accident disturb all respondents and are perceived as highly significant by different groups of the population. Radiation accident is a mental trauma with a complex configuration of traumatic effects that go beyond the limits of ordinary human experience. The obtained data will help to predict social disadaptation and will contribute to the creation of psycho-correctional and psychotherapeutic programs.